Obtenção e caracterização de perovskitas supercondutoras monocristalinas do tipo YxPr1-xBa2Cu3O7-δ dopadas por Fe, Ni, Ga e Zn - Cichetto Júnior, Leonélio (Universidade Federal de São Carlos, 2009)
The Praseodymium is known to have a singular behavior in the family of cuprate superconductors of high critical temperature of the type RE-123. When these cuprates are doped with Praseodymium apparently critical temperature decreases, with a metalinsulator transition. The origin of this behavior is of fundamental interest, and it may provide an explanation for the mechanism of superconductivity at high temperatures, since any reasonable theory for this mechanism must explain the behavior of the system Y1-xPrxBa2Cu3O7-δ, also called YPr-123. Through the experience gained by the research group to which we belong, and where this research project was developed, we continue the work begun by the PhD students Cecilia Stari and Alexandre Lanfredi. These two students have developed studies of polycrystalline YPr-123 family, and single crystals of YBa2Cu3O7-δ (Y-123) obtained by the method of Sol-Gel grown in crucibles of SnO2, respectively. None of them worked with the collection and characterization of single-crystalline samples of the system YPr-123, with special emphasis on Pr-rich samples, and that pure one, or PrBa2Cu3O7-δ (Pr-123). Studying to obtain and characterize samples of single-crystalline superconducting Pr-123 is the main goal of our Project Master. Besides obtaining samples of single-crystalline YPr-123 samples, in this master's work was studied the influence of cation doping in single crystals of composition Y1-xPrxBa2Cu3O7-δ (YPr123) for 0 ≤ x ≤ 1. Doping were performed with the elements Ga, Zn, Fe and Ni to study the behavior of superconductivity in these types of crystals. To obtain samples with a high degree of purity necessary for the study of their basic properties, were made our own SnO2 crucibles with high resistance to corrosion caused by self-flow used in the growth of crystals. Were also used Al2O3 and ZrO2CeO crucibles. The chemical composition and structural quality of these samples were analyzed by x-ray diffraction (XRD) and scanning electron microscopy (SEM) associated with the techniques of micro-analysis by energy dispersive X-ray (EDX). Also, we have used measures of the magnetic susceptibility for the characterization of superconducting properties of all samples. The results indicated that the whole YPr-123 family shows superconductivity, which is still very controversial in the literature. Specifically about the compound PrBa2Cu3O7-δ we verified that the sample is a superconductor, with critical temperature around 98K. This important result allows us to conclude that the relevant factor to observe the presence of superconductivity in this family is the Argon atmosphere during the growth of single crystal, as has been pointed out by previous publications of our research group. The results found here characterize this work as unique in the study of single crystal samples of the family YPr-123.
Keywords: Supercondutividade; Supercondutores de alta temperatura; Monocristal; Suscetibilidade magnética; CIENCIAS EXATAS E DA TERRA::FISICA